The antitumor action of endocannabinoids in the tumor microenvironment of glioblastoma - Tang, Yi; Wang, Maoru; Yu, Jiangping; Lv, Guangyao; Wang, Yu; Yu, Bin (Frontiers in Pharmacology, 2024)
Approximately 80% of all malignant brain tumors are gliomas, which are primary brain tumors. The most prevalent subtype of glioma, glioblastoma multiforme (GBM), is also the most deadly. Chemotherapy, immunotherapy, surgery, and conventional pharmacotherapy are currently available therapeutic options for GBM; unfortunately, these approaches only prolong the patient's life by five years at most. Despite numerous intensive therapeutic options, GBM is considered incurable. Accumulating preclinical data indicate that overt antitumoral effects can be induced by pharmacologically activating endocannabinoid receptors on glioma cells by modifying important intracellular signaling cascades. The complex mechanism underlying the endocannabinoid receptor-evoked antitumoral activity in experimental models of glioma may inhibit the ability of cancer cells to invade, proliferate, and exhibit stem cell-like characteristics, along with altering other aspects of the complex tumor microenvironment. The exact biological function of the endocannabinoid system in the development and spread of gliomas, however, is remains unclear and appears to rely heavily on context. Previous studies have revealed that endocannabinoid receptors are present in the tumor microenvironment, suggesting that these receptors could be novel targets for the treatment of GBM. Additionally, endocannabinoids have demonstrated anticancer effects through signaling pathways linked to the classic features of cancer. Thus, the pharmacology of endocannabinoids in the glioblastoma microenvironment is the main topic of this review, which may promote the development of future GBM therapies.